2012
DOI: 10.1016/j.ijgo.2012.05.019
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a novel training package among frontline maternal, newborn, and child health workers in South Sudan

Abstract: The MNCS package has led to improved FHW knowledge, skills, and referral. A novel package of training, checklists, and equipment can be successfully implemented in resource-limited settings and enhance links between community-based providers and healthcare facilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 11 publications
1
39
0
Order By: Relevance
“…The HBLSS program uses a cascade training approach, similar to other programs in which training extends across multiple levels of trainees and the numbers of people trained increases with each level (eg, health consultants, master trainers, and trainers). After receiving training, one level is responsible for training the next level down with support from higher levels, as needed . These programs differ in the extent to which they emphasize didactic or participatory methods such as hands‐on training and practice and follow‐up supervision after the initial training …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The HBLSS program uses a cascade training approach, similar to other programs in which training extends across multiple levels of trainees and the numbers of people trained increases with each level (eg, health consultants, master trainers, and trainers). After receiving training, one level is responsible for training the next level down with support from higher levels, as needed . These programs differ in the extent to which they emphasize didactic or participatory methods such as hands‐on training and practice and follow‐up supervision after the initial training …”
Section: Introductionmentioning
confidence: 99%
“…Health worker training programs have used a number of strategies to evaluate and demonstrate change in health workers’ skills and knowledge. Evaluation efforts have entailed (solely or in combination) pre‐ and posttraining knowledge tests, observation of skills by trainers, objective simulated clinical examinations, health worker self‐reports, and interviews with end users (community members who are the intended recipients of the care/education) . Some have also conducted evaluations a while after the posttraining to assess retention of knowledge and skills over time .…”
Section: Introductionmentioning
confidence: 99%
“…The current study demonstrated that the local trainers adequately managed the midwifery training and improved trainee's knowledge. As the effectiveness of training of trainers targeting nurses/midwives has been rarely reported (Nelson et al, 2012), this study contributes additional evidence. The local trainers could be key players in the expansion of the trainings throughout the State.…”
Section: ) Expansion Of Midwifery Trainings and Continuous Educationmentioning
confidence: 85%
“…The local trainers could be key players in the expansion of the trainings throughout the State. However, it should be noted that the improvements in outcomes were attained just after the training sessions, and the knowledge level was likely to drop to some extent over time (Nelson et al, 2012). Refresher training for midwives and periodical supervisory visits to PHCs by the trainers could contribute to the retention of skills as well as the knowledge obtained through the trainings.…”
Section: ) Expansion Of Midwifery Trainings and Continuous Educationmentioning
confidence: 99%
“…Additional details on the implementation, monitoring and evaluation of the programme will be published elsewhere. 28 …”
Section: Introductionmentioning
confidence: 99%